Conductive slurry for lithium ion battery and preparation method and application thereof
By combining SnO2/MXene composite with activated carbon particles and dispersion additives, conductive paste was prepared, which solved the problem of poor dispersion and stability of lithium-ion batteries, and achieved improved conductivity and stability of battery performance.
Patent Information
- Application Number
- CN202411770318.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-15
AI Technical Summary
The conductive agents in existing lithium-ion batteries have problems such as dispersion, poor stability, and easy shedding during charging and discharging, and complex conductive networks hinder the passage of lithium ions.
The conductive paste is prepared by combining SnO2/MXene composite material with activated carbon particles and dispersion additives (such as hydroxymethylcellulose, hydroxypropylcellulose), and mixing and dispersing treatment is carried out through stirring, ultrasonication, oscillation, etc.
It improves the conductivity and dispersion of the conductive paste, buffers the stress generated by the change in the electrode volume, builds a stable conductive network, promotes the rapid migration of electrons, and ensures the rate performance and cycle stability of the battery.
Smart Images

Figure CN119833202A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrode materials, and in particular to a conductive paste for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used as the main power source for mobile phones, tablet computers, laptops and other portable electronic products due to their relatively high energy density and relatively long cycle life. They are also gradually being used as the power source for hybrid vehicles, electric vehicles and electric non-motor vehicles. Lithium-ion batteries are mainly composed of a positive electrode, a negative electrode, a separator and an electrolyte. When the battery is connected through an external circuit, due to the different lithium chemical potentials of the positive and negative electrodes, chemical reactions take place on the electrodes, accompanied by the transfer of lithium ions inside the battery, while electrons form a current through the external circuit.
[0003] Since the positive and negative electrode materials of lithium-ion batteries generally have poor conductivity, the common solution includes adding conductive agents to the electrodes to enhance the electron transfer efficiency of the electrodes, thereby reducing the adverse effects of electrode polarization on the effective capacity of the active materials. MXene is a two-dimensional material with a graphene-like structure composed of alternating carbon layers and transition metal layers, which has a large specific surface area and excellent metal conductivity. Compared with traditional conductive agents, such as conductive carbon black, carbon nanotubes, graphene, etc., MXene has higher conductivity and the required dosage is relatively low. More importantly, as a new type of conductive material, MXene has a three-dimensional conductive skeleton constructed by the superposition of large sheet structures, which can promote the rapid migration of electrons. However, due to the large sheet structure and high specific surface area of MXene, there are strong van der Waals forces between MXene sheets, which makes MXene nanosheets irreversibly stacked and agglomerated, making it difficult to evenly disperse in the solvent, which seriously affects the conductivity, dispersibility and other properties of MXene conductive slurry. In addition, since the planar structure of MXene sheets can hinder the diffusion of lithium ions to a certain extent and extend the diffusion path of lithium ions, MXene conductive slurry can only be coated on the electrode in the form of a thin layer, which increases the risk of conductive agent falling off and increases the preparation process of the electrode. Summary of the invention
[0004] Based on this, the present invention provides a method for preparing a conductive slurry, and the application of the conductive slurry on the negative electrode of a lithium-ion battery, so as to solve the problems of poor dispersibility and stability of existing conductive agents, easy detachment from the electrode due to volume changes during charging and discharging, and complex conductive networks that hinder the passage of lithium ions.
[0005] To achieve the above object, the present invention provides a method for preparing a conductive paste for a lithium ion battery, which comprises the following steps:
[0006] S1. Add the etched single-layer MXene material and tin chloride pentahydrate into deionized water, disperse them evenly and place them in a reactor, react at 180-200°C for 12-24h, centrifuge, wash and dry the obtained product to obtain SnO 2 / MXene composites;
[0007] S2, adding one or both of hydroxymethyl cellulose and hydroxypropyl cellulose as dispersing aids into the N-methylpyrrolidone solution and mixing to obtain a mixed solution;
[0008] S3, the SnO 2 After grinding, the SnO / MXene composite material and activated carbon particles with a particle size of 500 nm-1 μm are added to the mixed solution of step S2, and mixed and dispersed by one or more methods of stirring, ultrasound, vibration, wet grinding, and ball milling to obtain a conductive slurry; the SnO 2 The mass ratio of / MXene composite material, activated carbon particles and dispersing aid is 1:(0.5-2):(10-50).
[0009] As a further preferred technical solution of the present invention, the MXene is Ti 3 C 2 、Ti 2 C. Ti 3 One or more of CN.
[0010] As a further preferred technical solution of the present invention, in step S1, the MXene material and SnCl 4 ·5H 2 The mass ratio of O is 1:1-2.
[0011] As a further preferred technical solution of the present invention, in step S1, MXene and SnCl 4 ·5H 2 O is added into deionized water at a mass ratio of 1:1-2, stirred into a 0.01-0.1 mol / L dispersion, and then placed in a reactor for reaction.
[0012] As a further preferred technical solution of the present invention, in step S1, the centrifugal speed is 2500-3000 r / min, and the centrifugal time is 5-10 min.
[0013] As a further preferred technical solution of the present invention, the SnO 2 The concentration of the / MXene composite material in the conductive slurry is 0.1-10 mg / mL.
[0014] As a further preferred technical solution of the present invention, the specific surface area of the activated carbon particles is 2000-2500m 2 / g.
[0015] According to another aspect of the present invention, the present invention also provides an application of a conductive paste in a lithium battery, wherein the lithium battery uses a negative electrode sheet using a SiOx-based material as an active material, and the conductive paste is coated on the surface of the negative electrode sheet as a conductive agent.
[0016] As a further preferred technical solution of the present invention, the coating thickness of the conductive paste is 500-1200 um.
[0017] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0018] 1) The conductive paste of the present invention fully utilizes SnO 2 / MXene composites have the advantages of electrical conductivity and further solve the problem of SnO 2 / MXene composite materials and activated carbon particles have problems in dispersion and storage stability. Moreover, compared with traditional conductive pastes, the amount required in applications is relatively low, which is conducive to saving materials, that is, reducing costs;
[0019] 2) The conductive slurry of the present invention can better promote the dispersion and stability of the system. When coated on the negative electrode, it can effectively buffer the stress generated by the change of the structural volume, build a stable conductive network, and promote the rapid migration of electrons, thereby ensuring the rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0021] Figure 1 The test curve of the cycle stability of the lithium-ion battery using the conductive paste prepared in Example 1;
[0022] Figure 2 This is a test curve of the charge and discharge efficiency of a lithium-ion battery using the conductive paste prepared in Example 1.
[0023] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0024] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0025] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0026] Example 1
[0027] A method for preparing a conductive paste comprises the following steps:
[0028] S1, SnO 2 Preparation of / MXene composites
[0029] A single MXene (Ti) sheet with a diameter of 3 μm was selected. 3 C 2 ), which can be etched by hydrofluoric acid MAX parent material (Ti 3 AlC 2 Or Ti 2 AlC) was prepared by stripping the Al atoms in the MXene or purchasing it through commercial channels; 140 mg MXene and 70 mg SnCl 4 ·5H 2 O was mixed and added into deionized water, and stirred into a 0.05 mol / L dispersion; the dispersion was put into a reactor, placed in a muffle furnace, heated to a reaction temperature of 180°C at a heating rate of 2°C / min, and reacted for 12 hours, and then cooled to room temperature at a cooling rate of 5°C / min. The obtained black product was separated by a centrifuge and repeatedly washed with deionized water and anhydrous ethanol, and the powder was collected and placed in a drying oven at 80°C for 12 hours to obtain SnO 2 / MXene composites;
[0030] S2, adding 5000 mg of hydroxymethyl cellulose to 10 ml of N-methylpyrrolidone solution and mixing to obtain a mixed solution;
[0031] S3, select specific surface area 2500m 2 / g, activated carbon particles (AC) with a particle size range of 500nm-1μm (average particle size 600nm); SnO 2 The / MXene composite material was ground for 1 h, and 100 mg SnO 2 The / MXene composite material was mixed with 200 mg of activated carbon particles and added to the above mixed solution, first stirred at a speed of 1000 r / min for 6 h, and then ultrasonicated at a power of 400 W for 1 h to obtain a conductive slurry.
[0032] Comparative Example 1
[0033] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that step S1 is omitted, that is, the SnO is replaced by a single-layer MXene raw material in step S3. 2 / MXene composite materials are directly used to prepare conductive slurry.
[0034] Comparative Example 2
[0035] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that the hydroxymethyl cellulose in step S3 is omitted, that is, the system without adding a dispersing aid is directly used to prepare the conductive paste.
[0036] Comparative Example 3
[0037] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that the activated carbon particles in step S3 are omitted, that is, the system without adding activated carbon particles is directly used to prepare the conductive paste.
[0038] The conductive paste samples prepared in Example 1 and Comparative Examples 1 and 2 were subjected to solid-liquid separation test (sedimentation test), and the phenomena observed after standing for 1 day, 7 days and 30 days were recorded respectively. Through observation: Comparative Example 2 had obvious solid-liquid separation phenomenon after standing for 1 day; while Example 1 and Comparative Examples 1 and 3 did not have solid-liquid separation phenomenon after standing for 30 days, indicating that the addition of hydroxymethyl cellulose in the system has the effect of improving the dispersibility of the sample, so that the sample has better storage stability; activated carbon particles.
[0039] The resistivity of fresh conductive paste samples (storage time not exceeding 6 hours) prepared in Example 1 and Comparative Examples 1 and 2 was tested by four-probe method. The resistivity of Comparative Example 1 was about 0.0006Ω / cm, the resistivity of Comparative Example 2 was less than 0.0001Ω / cm, the resistivity of Comparative Example 3 was 0.0003Ω / cm, and the resistivity of Example 1 was 0.0132Ω / cm. It can be seen from the comparison that no dispersing agent was added in Comparative Example 2, SnO 2 / MXene composite materials agglomerated together and not dispersed, resulting in poor dispersibility and extremely low resistivity; although a dispersing aid was added in Comparative Document 1, the MXene material could be evenly dispersed, but the electrochemical performance was still poor, and SnO 2 / MXene composite material, by depositing a thin layer of SnO on the surface of MXene 2 Nanoparticles, including SnO 2 It can provide more reactive sites for MXene, which can greatly improve the electrochemical performance. In addition, activated carbon particles have higher electrochemical performance. 2 / MXene composite material is used as a conductive adhesive. The MXene layer structure can wrap the activated carbon particles, and its single layer structure can fully contact with the activated carbon, thereby improving the electrochemical performance. Therefore, compared with Comparative Example 3 without adding activated carbon particles, the resistivity will be higher.
[0040] Embodiment 2-4
[0041] Compared with Example 1, the only difference between Examples 2-4 and Example 1 is that the amount of activated carbon particles added is adjusted to 50 mg, 100 mg and 300 mg respectively.
[0042] The conductive paste samples prepared in the above Examples 1-4 were applied to the battery to test the cycle stability and charge-discharge efficiency. A negative electrode sheet with SiOx-based material as the active material was used, and the conductive paste was applied as a conductive agent on the negative electrode sheet with a coating thickness of 500um. After vacuum drying at 80°C for 12 hours, the sheet was cut into a disc with a diameter of 15mm to obtain the corresponding negative electrode, and a lithium sheet was used as the counter electrode; the counter electrode, the negative electrode, etc. were assembled into a button battery. The specific test method is: after 10 cycles of constant current charge and discharge at a current density of 100mA / g, the current density was increased to 200mA / g and cycled to 100 cycles.
[0043] like Figure 1 and 2 As shown, the battery corresponding to Example 1 has a first charge specific capacity of 1369.8 mAh / g, a discharge specific capacity of 1788.2 mAh / g, a first charge and discharge efficiency of 76.6%, and a charge and discharge efficiency of 99.5% at the 100th week. In addition, in the cycle stability and charge and discharge efficiency tests of Examples 2-4, it was found that their first charge and discharge efficiencies were similar, but as the number of charging times increased, the charge and discharge efficiencies of Examples 2-4 at the 100th week were 85.3%, 91.5%, and 90.1%, respectively, and the changes were quite obvious. The results show that the negative electrode coated with the conductive slurry can ensure that the battery has a high cycle stability and capacity retention rate, and the charge and discharge efficiency can be maintained at a high level after 100 cycles of charge and discharge. This is because only the appropriate SnO 2 / MXene composite material and activated carbon particles in order to effectively form an efficient conductive network, thereby effectively improving the circulation effect of lithium ions and the electron conduction rate of the battery, and improving the reversible capacity of the battery under high-rate charge and discharge conditions. In addition, it is also related to the relative stability of the structure of the conductive slurry coating, which makes it difficult to fall off from the electrode during the charge and discharge process, resulting in repeated formation of SEI solidified film and consumption of lithium ions. However, the amount of activated carbon particles added will affect the structural stability of the conductive slurry coating. After a large number of experiments, when SnO 2 When the mass ratio of SnO / MXene composite material to activated carbon particles is greater than 1:2, the stability will deteriorate.2 The mass ratio of / MXene composite materials to activated carbon particles is 1:0.5-2, among which 1:2 is the best.
[0044] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a conductive paste for lithium-ion batteries, characterized in that: The following steps are involved: S1. Add the etched single-layer MXene material and tin chloride pentahydrate into deionized water, disperse them evenly and place them in a reactor to react at 180-200°C. Centrifuge, wash and dry the obtained product to obtain a SnO2 / MXene composite material; S2, adding one or both of hydroxymethyl cellulose and hydroxypropyl cellulose as dispersing aids into the N-methylpyrrolidone solution and mixing to obtain a mixed solution; S3, grinding the SnO2 / MXene composite material of step S1 and adding the activated carbon particles with a particle size of 500nm-1μm to the mixed solution of step S2, and mixing and dispersing the mixture by one or more methods of stirring, ultrasound, vibration, wet grinding, and ball milling to obtain a conductive slurry; The mass ratio of the SnO2 / MXene composite material, activated carbon particles and dispersing aid in the conductive slurry is 1:(0.5-2):(10-50).
2. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: The MXene is one or more of Ti3C2, Ti2C, and Ti3CN.
3. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: In step S1, the mass ratio of MXene material to SnCl4·5H2O is 1:1-2.
4. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: In step S1, MXene and SnCl4·5H2O are added to deionized water at a mass ratio of 1:1-2, stirred into a 0.01-0.1 mol / L dispersion, and then placed in a reactor for reaction.
5. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: In step S1, the centrifugal speed is 2500-3000 r / min, and the centrifugal time is 5-10 min.
6. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: The concentration of the SnO2 / MXene composite material in the conductive slurry is 0.1-10 mg / mL.
7. The method for preparing a conductive paste for lithium-ion batteries according to claim 1, characterized in that: The specific surface area of the activated carbon particles is 2000-2500m 2 / g.
8. Use of the conductive paste prepared by the method according to any one of claims 1 to 7 in lithium ion batteries.
9. The use of the conductive paste in a lithium-ion battery according to claim 8, characterized in that: The lithium-ion battery adopts a negative electrode sheet using SiOx-based material as an active material, and the conductive paste is coated on the surface of the negative electrode sheet as a conductive agent.
10. The use of the conductive paste in a lithium-ion battery according to claim 9, characterized in that: The coating thickness of the conductive paste is 500-1200 um.